Distress in suspected lung cancer patients following rapid and standard diagnostic programs: a prospective observational study. Issue 4 (9th September 2014) - Brocken, Pepijn; van der Heijden, Erik H. F. M.; Oud, Karen T. M.; Bootsma, Gerben; Groen, Harry J. M.; Donders, A. Rogier T.; Dekhuijzen, P. N. Richard; Prins, Judith B.
Abstract Objective Timeliness may influence emotional distress during the diagnostic phase of suspected lung cancer patients. We performed a prospective observational study to compare distress and quality of life (QoL) in two medical centres with a Rapid Outpatient Diagnostic Program (RODP) and two using conventional Stepwise Diagnostic Approach (SDA) on the basis of trained nurse‐led care. Methods Outpatients with radiological suspicion of lung cancer completed the Hospital Anxiety and Depression Scale (HADS), European Organization for Research and Treatment of Cancer 30‐item Quality of Life Questionnaire (QLQ‐C30) and its 13‐item Lung Cancer specific module (QLQ‐LC13) upon first visit, 2 days later, thereafter weekly for 5 weeks and after 3 months. Results The 72 SDA patients and 121 RODP patients had a mean pre‐diagnostic HADS‐total score of 13.5 (SD 7.6); 63.4% had a score ≥10. Baseline QLQ‐C30 global QoL was 61.6 (SD 22.7) exceeding reference values for lung cancer patients. Generalized least square models showed a significant centre by time interaction effect: during the first 6 weeks, HADS‐total scores decreased in RODP patients (13.8–11.9) but sustained in SDA patients (13.1–13.6), whereas QoL showed no relevant changes. Times to diagnosis and discussion of therapy plan for RODP patients were 7 and 11 days shorter, respectively. Conclusions Suspected lung cancer patients had high baseline distress levels. A decrease over time was found in RODP compared with SDA patients. QoL did not change relevantly. Albeit observational, these data indicate that patients experience less distress in rapid diagnostic programs than in stepwise diagnostic evaluation. Copyright © 2014 John Wiley & Sons, Ltd.